Diversity, Distribution and Status of the Amphibian fauna of Sangli district, Maharashtra, India - Sajjan MB; Jadhav BV; Patil RN (International Journal of Life Sciences, 2017)
30 species of amphibians were reported during a survey belonging to 19 genera of 9 families and 2 orders from Sangli district, Maharashtra, India, during June 2013 to May 2017. Out of 30 species recorded, 19 species are endemic to Western Ghats. All of the tehsils in this district except Shirala fall under semi arid zone having rich amphibian diversity. Shirala tehsil is flanked by Western Ghats with high rainfall and humidity harbouring highest number of species, while Atpadi tehsils is a drought prone zone with the lowest number of species. The highest numbers of species are reported at 1100m asl and the lowest number of species in the area below 600m asl. Along with checklist, information about the habitat, rainfall, temperature, distribution and status of amphibians in the district are given.